Exploring the Potential for a Hybrid Laundry Service in Jatinangor - Eugenia Efendy (Pelopor Publikasi Akademika, 2025)
This study explores the potential for a hybrid laundry service to address the unique challenges faced by the area’s predominantly student population. With students juggling academic and extracurricular commitments, the demand for convenient, reliable, and affordable laundry services remains unmet by existing providers, which are often criticized for delays, inconsistent quality, and limited accessibility. Through surveys, interviews, and the application of strategic frameworks such as the Segmenting-Targeting-Positioning (STP) model, Value Proposition Canvas, and Porter’s Five Forces, this research identifies key functional needs, such as affordability and speed, alongside emotional preferences like reliability and personalization. The findings highlight a significant market opportunity for a hybrid laundry service that integrates conventional full-service options with self-service facilities to offer flexibility, efficiency, and customer satisfaction. Additionally, a phased marketing strategy encompassing awareness, consideration, and conversion is proposed to effectively engage and retain the student demographic. This study concludes that a strategically designed and marketed hybrid laundry service can bridge gaps in affordability and quality, delivering a sustainable and impactful solution for the Jatinangor market.